The ITC International Handbook of Testing and Assessment 2016
DOI: 10.1093/med:psych/9780199356942.003.0017
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Rehabilitation and Health Assessments

Abstract: This chapter considers the types of measures used in rehabilitation and health settings, including their alignment with the major health and disease diagnostic and classification systems. The chapter provides an overview of the needs that are served by rehabilitation and health assessments and highlights the increasing importance of measures that yield data to guide decisions to support functioning across a broad range of life domains. It makes the case for prospective rehabilitation and health assessments tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…They indicated that the school curriculum and physical environments are not easy to negotiate, and the school social environments are also posing participation restrictions. Restrictive curriculum is a general‐education curriculum with no support services (Peterson, Mpofu & Oakland, ). This type of curriculum does not address the real learning needs of the learners with disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They indicated that the school curriculum and physical environments are not easy to negotiate, and the school social environments are also posing participation restrictions. Restrictive curriculum is a general‐education curriculum with no support services (Peterson, Mpofu & Oakland, ). This type of curriculum does not address the real learning needs of the learners with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, learners are required to adapt to the curriculum instead of the curriculum to adapt to the learners (Peterson, Mpofu & Oakland, ). A restrictive physical environment as discussed earlier in this study is a natural environment and human‐made changes to environment (Peterson, Mpofu & Oakland, ) that hinders selection of inclusive activities to partake by adolescents with physical disabilities (Loreman et al, ). For successful implementation of inclusion at school level, the curriculum and the physical environments must be least restrictive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies on MS have utilized generic health and well-being scales (e.g., Short Form Health Survey [SF-36]; Ware & Sherbourne, 1992; Sickness Impact Profile; Bergner, Bobbitt, Carter, & Gilson, 1981), and/or condition-specific instruments (e.g., MS Quality of Life Scale; Vickrey, Hays, Harooni, Myers, & Ellison, 1995) to measure social participation. Furthermore, these measures do not necessarily map across the broader ICF domain of activity and participation (Kwiatkowski et al, 2014; Mpofu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%